RELIGIOUS AND SOCIAL GROUP DIVERSITY IN BORROWING AND SPENDING BEHAVIOUR: ANALYSIS OF SURVEY RESULTS FROM RURAL WEST BENGAL, INDIA - Poddar Rana, Moumita; Banerjee (Chatterjee), Tanmoyee; Raychaudhuri, Ajitava (Economic Annals, 2023)
India is a nation characterised by diversity in religion and caste. This paper attempts to determine whether diversity among religious and social groups has any impact on the borrowing and spending behaviour of households in West Bengal, India. We conduct a Fairlie decomposition analysis to evaluate the religious and caste differences in the socio-economic variables that mostly contribute to the disparity in institutional borrowing, use of institutional loans, and use of banking services using a household-level primary survey in two districts of West Bengal, India. The results of the decomposition analysis in terms of social group differences and religious group differences show that households belonging to the unreserved category and the Hindu population are more likely to hold savings bank accounts, make use of institutional borrowing, and use loans for production purposes than different reserved categories and the Muslim population, respectively. The gap between the reserved and unreserved populations and the Hindu and Muslim populations in terms of institutional borrowing and the use of loans for production purposes widens for regular wage earners and casual labourers in nonagriculture. To reduce the gap between social and religious groups, occupation categories play a major role. The implication is that wider access to financial services should be provided to all sections of the population.